Resilient and Sustainable Semiconductor Supply Chains: Strategic Adaptations Amid Global Disruptions - Dr. Alexander M. Klein (Academic Reseach Library for International Journal of Computer Science & Information System, 2025)
The semiconductor industry occupies a pivotal role in the global economy, underpinning technological advancement and economic competitiveness across multiple sectors. Recent years have highlighted the fragility of semiconductor supply chains, exacerbated by geopolitical tensions, pandemics, and technological disruptions. This study investigates strategies for enhancing resilience and sustainability in semiconductor supply chains, focusing on supply chain reorganization, reshoring, financial flexibility, green practices, and human capital optimization. Using a comprehensive literature-based approach, the research integrates theoretical frameworks from sustainable supply chain management, operational risk management, and disruptive technology theory to derive actionable insights. The findings emphasize the importance of multi-dimensional resilience, highlighting the interconnectedness of operational, financial, and strategic factors. The analysis demonstrates that proactive investments in domestic production, talent portfolio management, and environmentally sustainable practices can mitigate systemic risks and foster long-term competitiveness. Additionally, the study examines the economic and operational implications of global shortages on critical industries such as automotive manufacturing, revealing the profound cost and strategic pressures arising from semiconductor scarcity. By synthesizing empirical insights with theoretical constructs, this research offers a nuanced understanding of the mechanisms through which semiconductor supply chains can adapt to uncertainty and disruption while promoting sustainable growth. The study concludes with recommendations for industry stakeholders, policymakers, and scholars, advocating for a holistic, integrated approach to supply chain resilience that balances efficiency, sustainability, and strategic autonomy.